2019
DOI: 10.3390/pathogens8010023
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori-induced DNA Methylation as an Epigenetic Modulator of Gastric Cancer: Recent Outcomes and Future Direction

Abstract: Gastric cancer is ranked fifth in cancer list and has the third highest mortality rate. Helicobacter pylori is a class I carcinogen and a predominant etiological factor of gastric cancer. H. pylori infection may induce carcinogenesis via epigenetic alterations in the promoter region of various genes. H. pylori is known to induce hypermethylation-silencing of several tumor suppressor genes in H. pylori-infected cancerous and H. pylori-infected non-cancerous gastric mucosae. This article presents a review of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 68 publications
1
36
0
Order By: Relevance
“…Bearing in mind that autophagy represents a tumor suppressor mechanism in the early stages cancer by preventing the excessive generation of ROS, as well as ensuing mitochondrial and DNA damage, the inhibition of autophagy by HpGGT can be expected to cause genome instability in H. pylori -infected gastric epithelial cells, which in turn generates a favorable environment for carcinogenesis [36]. Beyond genetic changes, it has been extensively described that epigenetic alterations mediated indirectly or directly by H. pylori infection play a major role in gastric cancer development [37,38,39,40]. In this context, it was recently reported that H. pylori -mediated autophagy inhibition involves modifying the expression of the autophagy-related gene ( Atg ) variant MAP1LC3Av1.…”
Section: Discussionmentioning
confidence: 99%
“…Bearing in mind that autophagy represents a tumor suppressor mechanism in the early stages cancer by preventing the excessive generation of ROS, as well as ensuing mitochondrial and DNA damage, the inhibition of autophagy by HpGGT can be expected to cause genome instability in H. pylori -infected gastric epithelial cells, which in turn generates a favorable environment for carcinogenesis [36]. Beyond genetic changes, it has been extensively described that epigenetic alterations mediated indirectly or directly by H. pylori infection play a major role in gastric cancer development [37,38,39,40]. In this context, it was recently reported that H. pylori -mediated autophagy inhibition involves modifying the expression of the autophagy-related gene ( Atg ) variant MAP1LC3Av1.…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicated that HP might cause the aberrant methylation of DNA-specific genes ( p16 and p57 ) and CpG island-specific genes ( hMLH1 , MINT1 , MINT2 , and MINT31) , which are important epigenetic mechanisms contributing to the HP-dependent lymphomagenesis of gastric MALT lymphoma (Table 1). In contrast to the epigenetic change-related genes of gastric MALT lymphoma, affected genes resulting from the HP-induced DNA methylation in the carcinogenesis of gastric cancer comprise cell adhesion pathway-regulated genes ( CDH1 , VEZT , CX32 , and CX43 ), cell cycle regulation-related genes ( CDKN2A, encoding the p16 INK4A protein), DNA mismatch repair genes ( MHL1 and MGMT ), inflammation-related genes ( TFF2 and COX-2 ), transcriptional factors-encoding genes ( RUNX3 , FOXD3 , USF1 , USF2 , GATA4 , and GATA5 ), autophagy-related genes ( ATG16L1 and MAP1LC3A ), and most tumor suppressor genes ( LOX , HRASLS , THBD , HAND1 , FLN , p41ARC , WWOX , CYLD , and PTEN ) [76].…”
Section: Epigenetic Changes and Genetic Changes Are Involved In Thmentioning
confidence: 99%
“…As a result, long-term colonization of H. pylori can damage the gastric mucosa causing various diseases of the upper gastrointestinal tract such as chronic gastritis, peptic ulcer, and gastric malignancies, particularly gastric cancer and gastric mucosa-associated lymphoid tissue (MALT) lymphoma [2,3]. H. pylori has been recognized as a Class I carcinogen by the International Agency for Research on Cancer [4] and as one of the strongest known risk factors for gastric malignancies [5,6,7,8]. Approximately 89% of all gastric cancers are attributed to H. pylori infection and the eradication of this infection has known to reduce gastric cancer incidence [9,10].…”
Section: Introductionmentioning
confidence: 99%